Protocol for development of a core outcome set for menopausal symptoms (COMMA). Issue 12 (December 2020) - Kim, Bobae V.; Iliodromiti, Stamatina; Christmas, Monica; Bell, Robin; Lensen, Sarah; Hickey, Martha
Abstract: Objective: Menopause is the natural cessation of menstruation and may be accompanied by troublesome symptoms including hot flushes and night sweats (vasomotor symptoms) and genitourinary symptoms. Randomized trials evaluating the safety and effectiveness of interventions for these symptoms have reported a wide range of outcomes and used inconsistent measures. This variation precludes comparing and combining data from different trials. To overcome this limitation, we will develop a Core Outcome Set for Menopausal Symptoms. Methods: We will systematically review the literature to identify the outcomes reported in the interventional trials for vasomotor and genitourinary symptoms. This list will be entered into a two-round modified Delphi survey to be completed by clinicians, researchers, and consumers (women who have experienced menopause). Participants will score outcomes on a nine-point scale from "not important" to "critically important." Representatives from each stakeholder group will then meet to discuss the results and finalize the Core Outcome Set. Ethics approval was not required as this was considered service evaluation and development. The study is registered with the Core Outcome Measures in Effectiveness Trials Initiative (http://www.comet-initiative.org/studies/details/917 ). Results: An agreed upon set of minimum outcomes and outcome measures will facilitate combining and comparing findings from future trials of treatments for menopausal symptoms. Conclusions: This Core Outcome Set will better enable women and clinicians to select effective treatments, improve the quality of trial reporting, reduce research wastage, and improve care for women with troublesome menopausal symptoms. Video Summary: http://links.lww.com/MENO/A633 .